Simulation Study and Experimental Verification of a Universal Contactless Battery Charging Platform With Localized Charging Features - Xun Liu; Hui, S.Y. (IEEE transactions on power electronics, 2007)
This paper presents a finite-element (FE) simulation study of a planar contactless battery charging platform for portable consumer electronic equipment. Magnetic field plots of the charging platform are generated under no-load and loaded conditions so that the field distribution of the planar charging platform can be visualized. Three working modes of the platform have been investigated and compared, including full excitation and two forms of selective excitation. With new results arising from this FE simulation study and practical experiments, the theory of the magnetomotive force (mmf) generation of the multilayer planar printed-circuit-board winding array structure can be further understood. The results obtained in this paper provide a foundation of understanding for future design and optimization of planar contactless charging platforms. In addition, it has been confirmed that an electromagnetic shield structure that has been applied to coreless planar transformer applications, can work equally well for the planar charging platform.